2019
DOI: 10.1016/j.annemergmed.2019.08.308
|View full text |Cite
|
Sign up to set email alerts
|

349 Comparison of Common Bile Duct Measurement by Point-of-Care Ultrasound to Radiology-Performed Ultrasound

Abstract: Study Objectives: Assess advanced practice provider (APP) competency in ultrasound (US) for symptomatic first trimester pregnancy after a targeted training protocol. Describe confidence of APPs in US image acquisition and interpretation. Methods: As part of a quality assurance (QA) initiative, APPs were trained in point-of-care (POC) first trimester pregnancy transabdominal ultrasound (TAU) via a didactic and supervised examinations. Prior to training, APPs did not utilize POCUS. This is a retrospective chart … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…One study found that the presence of biliary tree dilation was not significantly associated with the need for gall bladder surgery, but was a risk factor for unexpected return to the ED 13 . The remaining study found that there was no significant difference between the mean CBD diameter measured on POCUS and RADUS, but there was a poor correlation between the measurements of individual CBD diameters 49 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One study found that the presence of biliary tree dilation was not significantly associated with the need for gall bladder surgery, but was a risk factor for unexpected return to the ED 13 . The remaining study found that there was no significant difference between the mean CBD diameter measured on POCUS and RADUS, but there was a poor correlation between the measurements of individual CBD diameters 49 …”
Section: Resultsmentioning
confidence: 99%
“…11,32 Utility of POCUS measurement of the common bile duct Four studies examined the clinical significance of POCUS assessment of CBD dilation (Table 3). 13,[47][48][49] Two studies found that isolated CBD dilation, in the absence of other abnormal sonographic or laboratory findings, was associated with complicated biliary pathology requiring intervention in less than 2% of patients. 47,48 One study found that the presence of biliary tree dilation was not significantly associated with the need for gall bladder surgery, but was a risk factor for unexpected return to the ED.…”
Section: Diagnostic Accuracy Of Pocus and Radus Against A Mutual Refe...mentioning
confidence: 99%
See 1 more Smart Citation